2018
DOI: 10.1016/j.orgel.2017.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the molecular orientation of Ir(ppy)3 and Ir(ppy)2(acac) emitter complexes by X-ray diffraction

Abstract: Investigating the molecular orientation of Ir(ppy) 3 and Ir(ppy) 2 (acac) emitter complexes by X-ray diffraction, Organic Electronics (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…The influence of the PDM on the orientation of organometallic emitters has previously been a subject of intense discussion. [95,98,166,167] Purely organic fluorescent and TADF emitters are often of low symmetry and composed of donor and acceptor moieties that can lead to significant PDMs. However, this factor has not received much attention thus far in studies regarding the molecular orientation of purely organic emitters.…”
Section: New Directions From Electrostatic Interactionsmentioning
confidence: 99%
“…The influence of the PDM on the orientation of organometallic emitters has previously been a subject of intense discussion. [95,98,166,167] Purely organic fluorescent and TADF emitters are often of low symmetry and composed of donor and acceptor moieties that can lead to significant PDMs. However, this factor has not received much attention thus far in studies regarding the molecular orientation of purely organic emitters.…”
Section: New Directions From Electrostatic Interactionsmentioning
confidence: 99%
“…Moreover, random TDM orientation does not necessarily indicate random orientation of the symmetry axis of the molecule. For example, Murawski et al reported that the molecular orientation in the Ir(ppy) 3 film, which has a random TDM orientation [63]. On the other hand, SOP originates from the PDM orientation including its head-to-tail-direction, as it is proportional to ⟨cos θ⟩.…”
Section: Materials Exhibiting Sop and Their Characteristicsmentioning
confidence: 99%
“…Nevertheless, the water-insolubility of Ir­(ppy) 2 (acac) restricted its application in biosensing. Moreover, Ir­(ppy) 2 (acac) can self-assemble into amorphous aggregates with different sizes in different water fractions . Therefore, it is highly demanded to figure out how to control the formation of iridium self-assemblies with improved water solubility and dispersity for aqueous immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ir(ppy) 2 (acac) can self-assemble into amorphous aggregates with different sizes in different water fractions. 13 Therefore, it is highly demanded to figure out how to control the formation of iridium self-assemblies with improved water solubility and dispersity for aqueous immunoassays. Apoferritin (apoHSF) is a quasispherical protein nanocage of ferritin (from horse spleen) after removing the inside iron atoms.…”
Section: ■ Introductionmentioning
confidence: 99%